Enhancing Learning Support in Islamic Boarding Schools Post-COVID-19 with Participatory Action Research (PAR) Approach - Wajdi, Muh Barid Nizarudin; Rahim, Robbi; Nurmawati, Nurmawati; GS, Achmad Daengs; Lestari, Veronika Nugraheni Sri (Bisma : Bimbingan Swadaya Masyarakat, 2023)
This paper proposes a Participatory Action Research (PAR) framework to enhance learning support in Islamic boarding schools post-COVID-19. The framework consists of five stages: problem identification, planning, action, reflection, and evaluation, and is designed to ensure the involvement and engagement of all stakeholders in decision-making. The PAR approach was implemented in three pesantrens in East Java, Indonesia, involving 45 teachers, 90 students, and 60 parents. The results showed that the PAR approach enabled active participation and collaboration among stakeholders, leading to the identification of key challenges, development of an action plan, and implementation of various interventions. The reflection and evaluation stages allowed for continuous feedback and improvement, resulting in positive outcomes such as increased student engagement, improved teacher performance, and strengthened parent-school relationships. The findings suggest that the PAR approach can effectively enhance learning support in Islamic boarding schools post-COVID-19 and can be adapted in different contexts and settings. The proposed framework can serve as a model for reviving and revitalizing Islamic boarding school education post-COVID-19, and can help ensure sustainable development